2012
DOI: 10.6001/ekologija.v58i1.2349
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan parasites from genus Sarcocystis and their investigations in Lithuania

Abstract: The representatives of the genus Sarcocystis are cyst forming coccidian protozoa parasites broadly prevalent in mammals, birds and reptiles. Sarcocystis parasites are characterized by an obligatory prey-predator two-host life cycle. Currently, over 220 Sarcocystis species are known. Some of Sarcocystis species are pathogenic organisms dangerous to humans, domestic and wild animals. A harmful effect of Sarcocystis mainly occurs in intermediate hosts and depends on the species of parasite, infection intensity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 63 publications
1
25
1
3
Order By: Relevance
“…Previous molecular studies investigated the Sarcocystis species composition of roe deer, yielding four genetically characterized species. Only S. oviformis (Gjerde, 2012;Kolenda et al, 2014) was not found in our study whereas S. capreolicanis (Gjerde, 2012;Prakas & Butkauskas, 2012), S. gracilis (Gjerde, 2012;Kolenda et al, 2014), and S. silva (Gjerde, 2012;Kolenda et al, 2014) were found. This is also the first record of S. bovini, S. grueneri, S. miescheriana, S. taeniata, and S. truncata in this ungulate ( Figure S2a).…”
Section: Ungulate Sarcocystis Spp Faunacontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous molecular studies investigated the Sarcocystis species composition of roe deer, yielding four genetically characterized species. Only S. oviformis (Gjerde, 2012;Kolenda et al, 2014) was not found in our study whereas S. capreolicanis (Gjerde, 2012;Prakas & Butkauskas, 2012), S. gracilis (Gjerde, 2012;Kolenda et al, 2014), and S. silva (Gjerde, 2012;Kolenda et al, 2014) were found. This is also the first record of S. bovini, S. grueneri, S. miescheriana, S. taeniata, and S. truncata in this ungulate ( Figure S2a).…”
Section: Ungulate Sarcocystis Spp Faunacontrasting
confidence: 80%
“…We confirmed S. miescheriana (Kia, Mirhendi, Rezaeian, Zahabiun, & Sharbatkhori, 2011;Prakas & Butkauskas, 2012) but not the zoonotic S. suihominis (Prakas & Butkauskas, 2012) in our sample of wild boar ( Figure S2c). The fact that the supposedly suid-specific species S. miescheriana was also detected in cervids, and that S. miescheriana reads sequenced in this study had a higher intraspecific diversity than all other detected sarcocystis (Table S1), suggests that S. miescheriana sequences deposited in GenBank could potentially derive from more than the one species characterized to date.…”
Section: Ungulate Sarcocystis Spp Faunasupporting
confidence: 63%
“…Protozoan parasites of the genus Sarcocystis are cystforming coccidians having an obligatory two-host preypredator life-cycle [1,2]. Asexual multiplication occurs in the intermediate host (IH), whereas sexual multiplication takes place in the small intestine of the definitive host (DH) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Prakas et al, (2012) has currently reported that more than 220 Sarcocystis species were found. Sarcocystosis is now recognized as an emerging protozoan disease in animals (Srivastava et al, 1977) and man (Juyal and Bhatia, 1989;Shah, 1995) and it has generated interest among veterinary protozoologists all over the world.…”
Section: Resultsmentioning
confidence: 99%